Monetary financing: A response to Silke Tober - Andrew Watt (Intereconomics, 2015)
In the July/August issue of Intereconomics, Silke Tober criticised a proposal put forth by Andrew Watt to solve the euro crisis through the use of monetary fi nancing of the public sector. Tober argued that there are valid reasons to keep monetary and fi scal policy separate from one another and that Watt's proposal blurred the line between the two policy areas. Here, Watt responds to his critic, followed by a reply from Tober.
Keywords: 330